2004
DOI: 10.1042/bj20041102
|View full text |Cite
|
Sign up to set email alerts
|

Expression and refolding of Omp38 from Burkholderia pseudomallei and Burkholderia thailandensis, and its function as a diffusion porin

Abstract: In the present paper, we describe cloning and expression of two outer membrane proteins, BpsOmp38 (from Burkholderia pseudomallei) and BthOmp38 (from Burkholderia thailandensis) lacking signal peptide sequences, using the pET23d(+) expression vector and Escherichia coli host strain Origami(DE3). The 38 kDa proteins, expressed as insoluble inclusion bodies, were purified, solubilized in 8 M urea, and then subjected to refolding experiments. As seen on SDS/PAGE, the 38 kDa band completely migrated to approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 42 publications
1
15
0
1
Order By: Relevance
“…Little is known about porins and their possible roles in B. pseudomallei drug resistance. In vitro studies with B. pseudomallei Omp38 in reconstituted liposomes indicated that this protein functions as a diffusion porin for neutral sugars and charged antibiotics (Siritapetawee et al, 2004). Subsequent black lipid membrane reconstitution studies, liposome swelling assays and expression in a porin-deficient E. coli strain confirmed translocation of antibiotics through Omp38 and suggested a possible contribution of this porin in B. pseudomallei ceftazidime and carbapenem resistance (Aunkham et al, 2014; Suginta et al, 2011).…”
Section: Burkholderia Pseudomallei Complex Organismsmentioning
confidence: 99%
“…Little is known about porins and their possible roles in B. pseudomallei drug resistance. In vitro studies with B. pseudomallei Omp38 in reconstituted liposomes indicated that this protein functions as a diffusion porin for neutral sugars and charged antibiotics (Siritapetawee et al, 2004). Subsequent black lipid membrane reconstitution studies, liposome swelling assays and expression in a porin-deficient E. coli strain confirmed translocation of antibiotics through Omp38 and suggested a possible contribution of this porin in B. pseudomallei ceftazidime and carbapenem resistance (Aunkham et al, 2014; Suginta et al, 2011).…”
Section: Burkholderia Pseudomallei Complex Organismsmentioning
confidence: 99%
“…Most of these species contain a modified lipopolysaccharide, which results in polymyxin resistance (13). In addition, the permeability of the major outer membrane porin channel Omp38 appears to be low for antibiotics (14). The presence of a large number of multidrug efflux pumps, belonging to the resistance-nodulation-cell division (RND) superfamily, also plays a major role in the intrinsic resistance to a variety of antimicrobials.…”
mentioning
confidence: 99%
“…As shown in Fig. 2, the purified protein, which migrated as a band of 42 kDa on SDS-PAGE, was equivalent to Bps Omp38 isolated from the outer membrane of native Bps [22]. After purification, 1–2 mg of recombinant Bps Omp38 per litre of bacterial culture was obtained; this was 5–10 times higher than was obtained using the unfolding/refolding protocol [22].…”
Section: Discussionmentioning
confidence: 88%
“…2, the purified protein, which migrated as a band of 42 kDa on SDS-PAGE, was equivalent to Bps Omp38 isolated from the outer membrane of native Bps [22]. After purification, 1–2 mg of recombinant Bps Omp38 per litre of bacterial culture was obtained; this was 5–10 times higher than was obtained using the unfolding/refolding protocol [22]. Although in the E. coli BL21 (Omp8) Rosetta strain the genes encoding OmpF, OmpC, OmpA and LamB are disrupted [25], our previous study showed that this bacterium could still express a significant amount of endogenous OmpN, as a major contaminant [38].…”
Section: Discussionmentioning
confidence: 99%